The Effect of Administration of Immune Herbal Probiotics on Oxidative Stress Profile and Performance of KUB 2 Chickens: Pengaruh Pemberian Probiotik Herbal Imun terhadap Profil Stres Oksidatif dan Performa Ayam KUB 2 - Seno, Haris; Nurul Humaidah; Umi Kalsum (UNIVERSITAS ISLAM LAMONGAN, 2025)
Immune herbal probiotics are nutrients containing probiotics and enzymes. The purpose of this study was to evaluate the effect of administering immune herbal probiotics on the oxidative stress profile and performance of KUB 2 chickens. The research materials were 192 KUB-2 male chickens aged 21 days and immune herbal probiotics. The research method used was an experimental method. There were 4 treatments with 4 repetitions. The treatments given were P0 = Control, P1 = 2 ml/L immune herbal probiotics, P2 = 4 ml/L, P3 = 6 ml/L. The variables measured were Oxidative Stress Profile and net gain. Data were analyzed using ANOVA. The results showed that administering immune herbal probiotics had a very significant effect (P<0.01) on SOD activity and MDA levels and had no significant effect (P>0.05) on Net Gain. The average value of SOD activity (mmol/L) was P0: 47.00a, P1: 14.33b P2: 31.72bc and P3: 43.94c. The average MDA level (mmol/L) was P0: 6.28a, P1: 48.69a, P2: 41.11b and P3: 14.51b. The average body weight gain was P0: 0.73 grams, P1: 0.76 grams, P2: 0.81 grams and P3: 0.77 grams. The conclusion of the study was that the administration of Immune Herbal Probiotics affected SOD activity and MDA levels in KUB 2 Chickens.